The effect of the missouri mathematics project learning model on students' mathematical problem-solving ability on circle material - Siti Zia Hadatul Hasanah; Nur Ainun Lubis (Universitas Islam Negeri Raden Intan Lampung, 2025)
Mathematics plays an important role in improving students' mathematical problem-solving abilities. However, mathematics learning using conventional learning models often fails to stimulate an increase in students' mathematical problem-solving abilities. This study investigated the effect of the Missouri Mathematics Project (MMP) learning model on students' mathematical problem-solving abilities. This study used a quasi-experimental method with a quantitative approach. The population in this study included all eighth-grade students of UPT SPF SMP Negeri 8 Percut Sei Tuan with a total of 185 students. This study involved an experimental class taught using the Missouri Mathematics Project learning model and a control class with a conventional learning model. The results showed that the mathematical problem-solving abilities of students who used the Missouri Mathematics Project (MMP) learning model improved more than those who used the conventional learning model. This indicates that the Missouri Mathematics Project (MMP) learning model has an effect on students' mathematical problem-solving abilities.